Urine stem cells are equipped to provide B cell survival signals. (13th February 2021) - Zidan, Asmaa A.; Perkins, Griffith B.; Al‐Hawwas, Mohammed; Elhossiny, Ahmed; Yang, Jianyu; Bobrovskaya, Larisa; Mourad, Ghada M.; Zhou, Xin‐Fu; Hurtado, Plinio R.
Abstract: The interplay between mesenchymal stem cells (MSCs) and immune cells has been studied for MSCs isolated from different tissues. However, the immunomodulatory capacity of urine stem cells (USCs) has not been adequately researched. The present study reports on the effect of USCs on peripheral blood lymphocytes. USCs were isolated and characterized before coculture with resting and with anti‐CD3/CD28 bead stimulated lymphocytes. Similarly to bone marrow mesenchymal stem cells (BM‐MSCs), USCs inhibited the proliferation of activated T lymphocytes and induced their apoptosis. However, they also induced strong activation, proliferation, and cytokine and antibody production by B lymphocytes. Molecular phenotype and supernatant analysis revealed that USCs secrete a range of cytokines and effector molecules, known to play a central role in B cell biology. These included B cell‐activating factor (BAFF), interleukin 6 (IL‐6) and CD40L. These findings raise the possibility of an unrecognized active role for kidney stem cells in modulating local immune cells. Abstract : Kidney derived urine stem cells are equipped to provide B cells survival signals, promoting their activation, proliferation, and antibody production. Molecular phenotype and supernatant analysis revealed that USCs express the adhesion molecule ICAM‐1 and secrete B cell‐activating factor (BAFF), interleukin 6 (IL‐6) and CD40L, raising the possibility of an unrecognized active role for these cells in modulating local immune cells.